Gambaran Erupsi Molar Satu Permanen Mandibula dan Status Gizi Anak Usia 6 Tahun - Kapugu, Tamariska; Khoman, Johanna A.; Kawengian, Shirley E. S. (e-GiGi, 2025)
Abstract: Tooth eruption is an important process in child's growth. Good nutritional status plays a crucial role in the growth process of children, including the growth of teeth and bones. This study aimed to describe the eruption of the permanent mandibular first molar and the nutritional status of 6-year-old children at Desa Poopoh. This was a descriptive study with a cross-sectional design. Samples were taken using a total sampling technique with inclusion criteria for all 6-year-old children at Poopoh Village, totaling 32 children. This study assessed the eruption of the permanent mandibular first molar and examined their nutritional status by measuring their weight and height. The results showed that 78.12% of the children had erupted permanent mandibular first molars. The nutritional status based on height-for-age (HAZ) showed 25.0% of stunted and 75.0% of normal categories. The nutritional status based on BMI-for-age (BAZ) showed 12.5% underweight, 71.8% normal, 9.38% overweight, and 6.25% obese. In conclusion, the majority of 6-year-old children at Desa Poopoh have erupted permanent mandibular first molars, and normal H/A and BMI/A nutritional status. Keywords: tooth eruption; permanent mandibular first molar; nutritional status Abstrak: Erupsi gigi menjadi salah satu proses penting dalam pertumbuhan anak. Status gizi yang baik berperan penting dalam proses pertumbuhan anak, termasuk pertumbuhan gigi dan tulang. Penelitian ini bertujuan untuk mengetahui gambaran erupsi molar satu permanen mandibula dan status gizi anak usia 6 tahun di Desa Poopoh. Jenis penelitian ini merupakan penelitian deskriptif menggunakan desain potong lintang. Pengambilan sampel menggunakan teknik total sampling dengan kriteria inklusi terhadap seluruh anak usia 6 tahun di Desa Poopoh yang berjumlah 32 anak. Pada penelitian ini dilakukan penilaian erupsi gigi molar satu permanen mandibula pada rongga mulut anak dan pemeriksaan status gizi anak mulai dari pengukuran berat badan dan tinggi badan pada anak. Hasil pemeriksaan menunjukkan gigi molar satu permanen mandibula yang sudah erupsi sebesar 78,12%. Status gizi berdasarkan TB/U didapatkan kategori pendek/stunted (25,0%) dan kategori normal (75,0%). Status gizi berdasarkan IMT/U didapatkan kategori kurus (12,5%), normal (71,8%), gemuk (9,38%), obesitas (6,25%). Simpulan penelitian ini ialah mayoritas anak usia 6 tahun di Desa Poopoh sudah mengalami erupsi gigi molar satu permanen mandibula, dengan kategori status gizi TB/U dan IMT/U normal. Kata kunci: erupsi gigi; molar satu permanen mandibula; status gizi